Persistent Stapedial Artery Encountered during Cochlear Implantation. (22nd February 2022) - Jones, Holly; Hintze, Justin; Gendre, Adrien; Wijaya, Clifton; Glynn, Fergal; Viani, Laura; Walshe, Peter
Abstract : Objectives . Persistent stapedial artery (PSA) is a rare congenital anomaly that can complicate middle ear surgery. Methods . We present the case of a 25-year-old male who underwent right-sided cochlear implantation. A PSA was encountered lying over the middle promontory intraoperatively. Results . The PSA was carefully lifted off the middle ear promontory using a Hughes elevator to divide adhesions and delineate the artery. The implant electrode was placed through the round window niche in the usual fashion. Tragal cartilage and fibrin glue were used to control the trajectory of the electrode. Conclusion . Cochlear implantation can be performed safely in patients with PSA.